Noken Voting System in the Yahukimo Regency Election, Papua: An Analyzes - Silalahi, Rio Aldino Yosevan; Zainulla, Pandu Satriawan (CV. Era Digital Nusantara, 2024)
Abstract: The utilization of the noken voting system in general elections within Yahukimo Regency, Papua Province, is deeply rooted in Papuan cultural traditions, specifically employing bags made from orchid fiber. However, its incorporation into the electoral process has raised concerns regarding its compatibility with democratic principles and constitutional legality. Purpose: This study aims to examine the constitutionality of the noken voting system in Yahukimo Regency, Papua, particularly focusing on its adherence to democratic principles and the secrecy of votes. Design/Methodology/Approach: a normative legal research approach, this study analyzes primary and secondary legal sources to evaluate the legal framework surrounding the noken system. The examination delves into its alignment with constitutional principles and electoral laws. Findings: The noken system, while significant culturally, poses challenges to the secrecy principle crucial to democratic elections. Its open display of votes contradicts constitutional mandates for free, fair, and secret elections. Despite Constitutional Court validation, concerns persist regarding its compatibility with democratic norms and constitutional standards. Originality/value: This research contributes to the discourse on the intersection of cultural heritage and democratic principles, particularly in the context of electoral processes. It underscores the necessity for legal enhancements to ensure the harmonization of the noken system with democratic and constitutional imperatives.